Inclusion of Anastrepha ludens fruit fly pupae in poultry rations added with digestive enzymes and yeast - López-García, José Alfonso; Grajales-Conesa, Julieta; Albores-Flores, Víctor Jesús; Torres de los Santos, Rodolfo; Ramón-Javier, Luis Alejandro; Cordova-Albores, Liliana Carolina (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2021)
In Mexico, poultry meat represents 24,8 % of the protein consumed. In the search for protein sources that meet this demand, the use of insects has been found to be of potential interest. In order to reduce the effect of the components that affect the absorption of nutrients, additives such as digestive enzymes and microorganisms have been used. The objective of this study was to determine the weight gain of birds (Gallus gallus domesticus) fed with diets formulated with fruit fly pupa (Anastrepha ludens), digestive enzymes and yeast (Saccharomyces cerevisiae). Groups were established completely at random with different inclusions of fly pupae 0 %, 12 %, 14 % and 16 % respectively and significant differences were found (p<0.05). The group with 14 % protein was the one with the greatest weight gain during the experiment and the second phase used digestive enzymes and Saccharomyces cerevisiae and it was found that treatment 3: 14 % of Anastrepha ludens pupa + 200 IU of Protease + 1502 IU of Amylase + 80 IU of Cellulase + 62 IU of Lipase + 40 IU of Pectinase + 8.88x109 CFU S. cerevisiae / 100 g of feed showed differences (p<0.05) and the best results in the weight gain of the birds. It is concluded that inclusion of 14 % of fly pupa in rations promotes the weight gain of Gallus gallus domesticus with the addition of digestive enzymes and S. cerevisiae.